Military, sailors and the sick poor. Contribution to the history of the San Juan de Dios hospital in Cartagena de Indias (18th century) (2008)
This article explores the history of the San Juan de Dios Hospital in Cartagena de Indias, at the end of the 18th century. Its activities and evolution cannot be understood unless they are analyzed within the context of the Bourbon sanitary reforms. It was precisely at that time when these reforms were being implemented in Nueva Granada. One of the goals of the reforms was to improve the health of the population in order to discipline the vassals, to promote the growth of the workforce and to increase the Crown's wealth. The text reviews different aspects of the institution, and how it operated. It examines its budget, its expenses, and the dynamics of the hospital population and of its employees. In doing so, it intends to explain what the hospital offered to the city's various social groups.